Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s10681-008-9856-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and histological characterization of a novel recessive genic male sterile line of Brassica napus derived from a cross with Capsella bursa-pastoris

Abstract: In a previously made cross Brassica napus cv. Oro (2n = 38) 9 Capsella bursa-pastoris (2n = 4x = 32), one F 1 hybrid with 2n = 38 was totally male sterile. The hybrid contained no complete chromosomes from C. bursa-pastoris, but some specific AFLP (amplified fragment length polymorphism) bands of C. bursa-pastoris were detected. The hybrid was morphologically quite similar to 'Oro' except for smaller flowers with rudimentary stamens but normal pistils, and showed good seed-set after pollination by 'Oro' and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Several similar studies have reported genotypic differences in PUE and PAE across multiple crop species (see recent reviews by Shenoy and Kalagudi, 2005; Wang et al, 2010). In addition, a limited number of studies have reported Quantitative Trait Loci (QTL) for PUE (Wissuwa et al, 1998; Su et al, 2006; Chen et al, 2009). …”
Section: Internal Phosphorus Use Efficiency As a Key Traitmentioning
confidence: 99%
“…Several similar studies have reported genotypic differences in PUE and PAE across multiple crop species (see recent reviews by Shenoy and Kalagudi, 2005; Wang et al, 2010). In addition, a limited number of studies have reported Quantitative Trait Loci (QTL) for PUE (Wissuwa et al, 1998; Su et al, 2006; Chen et al, 2009). …”
Section: Internal Phosphorus Use Efficiency As a Key Traitmentioning
confidence: 99%
“…The PCR reaction was performed at 94°C for 5 min, followed by 35 cycles of 94°C for 30 s, 47°C for 30 s and 72°C for 45 s, with a final extension for 10 min at 72°C. The PCR products were analyzed by electrophoresis in 6% polyacrylamide gels, and DNA fragments were visualized by silver staining (Bassam et al 1991;Chen et al 2009). …”
Section: Molecular Marker Analysis and Linkage Map Constructionmentioning
confidence: 99%
“…The epistatic suppressor gene was widespread in Brassiceae. A tri-genetic inheritance model, later proposed to interpret sterility inheritance in 9012AB, suggests that male sterility is controlled by the interaction of two recessive male-sterile genes (Bnms3 and Bnms4) with an epistatic suppressor gene (BnRf or BnEsp) (Chen et al, 1998). In other reports on B. napus (Song et al, 2006) and B.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted February 26, 2024. ; https://doi.org/10.1101/2024.02.25.581914 doi: bioRxiv preprint male-sterile genes (Bnms3 and Bnms4) with an epistatic suppressor gene (BnRf or BnEsp) (Chen et al, 1998). In other reports on B. napus (Song et al, 2006) andB.…”
Section: At5g50260 (Cep1 Cysteine Endopeptidase 1) Was the Correspond...mentioning
confidence: 98%